Analisis SWOT dan Strategi Pemasaran Produk Talangan Kesehatan pada KSPPS BMT Aman Utama Jepara - Sadid, Diva Mustamar; Ansori, Miswan (Universitas Islam Negeri Alauddin Makassar, 2024)
The purpose of this study was to identify effective marketing strategies for Health Talangan products at KSPPS BMT Aman Utama Jepara using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Health development in Indonesia is a collective effort to achieve optimal public health, which requires cross-sector collaboration and continuity from previous efforts. Despite increasing life expectancy, health challenges remain, especially with high rates of disease and the impact of the COVID-19 pandemic. Data from the Basic Health Research (Riskesdas) is used to form the Community Health Development Index, which assesses the health of each region. Jepara district, which has a low GPA in Central Java, faces challenges in improving health services. The Health Talangan product innovation by KSPPS BMT Aman Utama Jepara aims to reduce health costs for its members. This study aims to determine the right marketing strategy for the product by analyzing the existing strengths, weaknesses, opportunities, and threats. Combined with the calculation of IFAS (Internal Factors Analysis Summary) and EFAS weight values (External Factors Analysis Summary). This method also includes interviews, observations, and documentation. From the calculation with IFAS and EFAS approach, the marketing strategy of health food products is at the coordinate point of Quadrant I, which is entering into the classification of growth strategies.